Pengaruh Berkumur Rebusan Daun Sirih Merah Terhadap Indeks PHP-M pada Masyarakat Desa Sawang Kecamatan Sawang Kabupaten Aceh Utara - Zarrahan Zurra (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Dental and oral hygiene is an important factor in preventing caries and periodontal disease. One of the efforts that can be made to control plaque is the use of natural mouthwashes such as red betel leaves (Piper crocatum Ruiz & Pav.) which contain antibacterial compounds. This study aims to determine the effect of gargling using red betel leaf boiled water on the decrease in the Personal Hygiene Performance Modified (PHP-M) index in the people of Sawang Village, Sawang District, North Aceh Regency. This study uses a quasi experimental design with a nonequivalent control group design. The research sample amounted to 68 respondents aged 12–15 years who were divided into an experimental group (34 respondents) and a control group (34 respondents). The experimental group gargled using 20 ml of red betel leaf boiled water for 30 seconds twice a day for 7 days, while the control group gargled using water. Measurements of the PHP-M index were carried out before and after the intervention. Data analysis was conducted using Paired T-Test and Independent T-Test. The results showed that the average PHP-M index in the experimental group decreased from 39.29 to 22.35 with a decrease of 16.94 points and a p<0.001 value. In the control group, the average PHP-M index decreased from 36.97 to 36.62 with a difference of 0.35 points and a p=0.564 value. The Independent T-Test showed that the average post-test score of the experimental group was lower than that of the control group with p<0.001. It can be concluded that gargling using red betel leaf decoction has a significant effect on the reduction of the PHP-M index and may be used as an alternative natural mouthwash.